Combination of Crusted Scabies with Bullous Scabies: A Rare Case - Asnawi V; Maulida M; Hidayati A; Gunawan H; Dwiyana RF; Hindritiani R (International Medical Case Reports Journal, 2023)
Vella Asnawi,1,2 Mimi Maulida,1,2 Arie Hidayati,1,2 Hendra Gunawan,3,4 Reiva Farah Dwiyana,3,4 Reti Hindritiani3,4 1Department of Dermatology and Venereology, Faculty of Medicine, Universitas Syiah Kuala, Banda Aceh, Aceh, Indonesia; 2Department of Dermatology and Venereology, Dr. Zainoel Abidin General Hospital, Banda Aceh, Aceh, Indonesia; 3Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 4Department of Dermatology and Venereology, Hasan Sadikin General Hospital, Bandung, West Java, IndonesiaCorrespondence: Vella Asnawi, Department of Dermatology and Venereology, Dr. Zainoel Abidin General Hospital, Jl. Tgk.Daud Beureueh No. 108, Banda Aceh, Aceh, Indonesia, Tel +6281938199931, Email vella.spkk@gmail.comAbstract: Scabies is a parasitic skin disease caused by Sarcoptes scabiei var. hominis. Crusted scabies, also known as Norwegian scabies, is a rare and severe form of scabies that occurs more frequently in immunocompromised, elderly, disabled, and debilitated patients. The present study reports a case of crusted scabies combined with bullous scabies. A 44-year-old man was admitted with the chief complaint of red, thick, scaly patches of skin accompanied by crusting that felt itchy and worsened at night. The lesions had appeared all over his body intermittently for the last 10 years; however, the complaints worsened in the last 2 months. From dermatological status, the anterior and posterior thoracic regions and between the fingers of both hands showed generalized distribution of erythematous, yellowish, hyperkeratotic plaques with clear boundaries, pustules, and blisters on an erythematous base with multiple erosions and excoriations. S. scabiei were found on skin scraping examination, and histopathological examination supported the diagnosis of bullous scabies. The patient received 5% permethrin lotion topical therapy and systemic ivermectin therapy. In addition, the patient was given systemic antibiotics. The lesions improved after 2 weeks of therapy, and no S. scabiei were found on the subsequent microscopic examination. Treatment with a combination of topical and systemic scabicidal agents produced a favorable outcome in this patient.Keywords: Norwegian scabies, bullous, permethrin, ivermectin, Sarcoptes